The nature and causes of children's grammatical difficulties: Evidence from an intervention to improve past tense marking in children with Down syndrome. Issue 4 (23rd January 2022) - Baxter, Rebecca; Rees, Rachel; Perovic, Alexandra; Hulme, Charles
Abstract: Children with language learning difficulties frequently display problems learning grammar. One such group is children with Down syndrome. This study evaluates the effectiveness of an intervention to teach the use of the regular simple past tense to children with Down syndrome. Trained teaching assistants delivered the intervention for 20 min per day for 10 weeks. We conducted a Randomised Controlled Trial, with a waiting list control design in which the Intervention group ( N  = 26) received the intervention immediately, while the delayed intervention group ( N  = 26) received the intervention later. Immediately following the intervention, the intervention group showed significantly larger gains in the use of regular simple past tense forms ( d  = 1.63 on a composite measure of simple past tense formation) as well as generalisation to verbs not explicitly taught. In addition, following the intervention children made overregularisation errors by incorrectly using regular simple past tense marking for irregular verbs; such errors support the claim that children had acquired generative knowledge underlying past tense marking. The delayed intervention control group showed identical benefits from the intervention when they received it, and the gains shown by the intervention group were maintained at follow up testing. This study shows that children with Down syndrome, who display severe language difficulties, can be taught to use simple past tense marking. The theoretical and applied implications of these findings for understanding the nature, causes and treatments of children's language difficulties are discussed. Abstract : A plot showing improvements in the use of regular simple past tense forms in children with Down syndrome as a function of time and intervention. At time 2 (t2) the intervention group showed significantly larger gains after receiving the intervention compared to the delayed intervention group who had not yet received the intervention. At t3, after both groups had received the intervention, the intervention group maintained their gains whilst the delayed intervention showed comparable improvements